Effects of probiotic supplementation on inflammatory biomarkers and uremic toxins in non-dialysis chronic kidney patients: A double-blind, randomized, placebo-controlled trial. (July 2018) - de Faria Barros, Amanda; Borges, Natália A.; Nakao, Lia Sumie; Dolenga, Carla J.; do Carmo, Flavia Lima; de Carvalho Ferreira, Dennis; Stenvinkel, Peter; Bergman, Peter; Lindholm, Bengt; Mafra, Denise
Graphical abstract: Probiotic supplementation could be not a good strategy for dysbiosis in nondialysis CKD patients. Highlights: Supplementation with probiotics showed no benefit in reducing inflammation and uremic toxins. The probiotics increased levels of the pro-inflammatory cytokine IL-6 after 3 months. Supplementation with probiotic should be given with caution to non-dialysis CKD patients. Abstract: Probiotics may mitigate the generation of uremic toxins and inflammatory biomarkers. The aim of this study was to evaluate the effects of probiotics on uremic toxins and inflammatory biomarkers in CKD. In this randomized, double-blind, placebo-controlled trial, 30 patients (63.8 ± 7.5 years, 14 men, mean BMI of 27.2 ± 3.8 kg/m 2 ) were assigned to receive one of two treatments: probiotics (n = 15; Streptococcus thermophilus, Lactobacillus acidophilus and Bifidobacteria longum -90 billion CFU per day) or placebo (n = 15) daily for three months. Plasma uremic toxins were measured using reversed-phase liquid-chromatography (RP-HPLC); choline, betaine and trimethylamine-N-oxide (TMAO) were measured using liquid chromatography–mass spectrometry (LC-MS/MS); and inflammatory biomarkers were measured using ELISA. Uremic toxins were not influenced by the probiotics; however, IL-6 levels increased significantly from 15.6 (14.8–20.8) pg/mL to 23.0 (17.6–29.6) pg/mL, p = 0.01. There was a positive correlation between the levels of p-cresyl sulfate and urea (r = 0.55; p = 0.02) and between TMAO and CRP (r = 0.46; p = 0.05) at baseline. These data suggest that probiotic supplementation did not result in expected benefits for non-dialysis CKD patients.